Functional characterization of a GFAP variant of uncertain significance in an Alexander disease case within the setting of an individualized medicine clinic. Issue 9 (15th August 2016) - Boczek, Nicole J.; Sigafoos, Ashley N.; Zimmermann, Michael T.; Maus, Rachel L.; Cousin, Margot A.; Blackburn, Patrick R.; Urrutia, Raul; Clark, Karl J.; Patterson, Marc C.; Wick, Myra J.; Klee, Eric W.
Key Clinical Message: A de novo GFAP variant, p.R376W, was identified in a child presenting with hypotonia, developmental delay, and abnormal brain MRI. Following the 2015 ACMG variant classification guidelines and the functional studies showing protein aggregate formation in vitro, p.R376W should be classified as a pathogenic variant, causative for Alexander disease. Abstract : A de novo GFAP variant, p.R376W, was identified in a child presenting with hypotonia, developmental delay, and abnormal brain MRI. Following the 2015 ACMG variant classification guidelines and the functional studies showing protein aggregate formation in vitro, p.R376W should be classified as a pathogenic variant, causative for Alexander disease.